(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
It is not an exaggeration to say that Abdulla Avloni, a mature scientist and pedagogue, brought a number of changes and updates to the field of education and science and the teaching process through his innovative actions and pedagogical views. In the course of this article, we will study the pedagogical views of Abdulla Avloni and the issue of education in his works.